Continuous Anaerobic Digestion of Wood Vinegar Wastewater From Pyrolysis: Microbial Diversity and Functional Genes Prediction - Hua, Dongliang; Fan, Qingwen; Zhao, Yuxiao; Xu, Haipeng; Chen, Lei; Si, Hongyu; Li, Yan (Frontiers in Bioengineering and Biotechnology, 2020)
At present, anaerobic digestion (AD) is a suitable method for energy recovery and recycling of organic wastes. AD of wood vinegar wastewater (WVWW), characterized by abundant organic matter involves significant potential for energy sustainability. Therefore, in this study, continuous methane generation from WVWW is investigated. Granular sludges at diverse organic loading rates (OLRs) are sampled, and structures and functional genes predicted for bacterial communities are analyzed. The results reveal that toxic substances in the WVWW significantly reduce daily methane production and biodegradability (BD) at >8.58 g COD/L·d. The samples are dominated by phyla Chloroflexi, Firmicutes, Proteobacteria, Acidobacteria, Synergistetes, and Actinobacteria. The bacterial structures considerably vary with OLRs at the genus level, indicating that selective functional genes enrichment is possible through long-term continuous AD. In addition, the functional genes predicted can serve as basis for understanding the metabolic mechanism of organics.